Causal Model of Factors Influencing Decisions to Become an E-Sport Player - Wantayakul , Nathayu; Decha, Oraphan; Whangmahaporn, Benya (Journal of Ecohumanism, 2025)
Background. The athletes must possess internal drive and external pressures, such as environmental factors to navigate them through or overcome various obstacles on their journey towards developing into professional esports players. Objective. to explore causal model of factors influencing decisions to become an E-Sport player. Methods. The study research was mixing method study the qualitative research was used to employs explore causal model of factors influencing decisions to become an E-Sport player. The focus group was used in the qualitative phase with E-sport professional athletes who have an experience more than three years in competing E-sport both domestic and international tournament all total 10 people to explore the motivations of becoming professional esports players with the Value and Lifestyles (VALS) Framework concept. Next, the quantitative was used for obtaining direct and indirect effects of causal factors influencing the decision to become an esports athlete in Thailand. The sample size number of participants was 400 individuals answering the questionnaire and the answers were analyzed preliminary data using descriptive statistics includes percentages, averages, standard deviations, maximum and minimum values, skewness, and kurtosis. Additionally, the researchers utilized the LISREL model to analyze causal factors influencing the decision to become an esports athlete. The study also examined the direct and indirect effects of causal factors influencing the decision to become an esports athlete in Thailand using Pearson’s correlation coefficient. Result. The intention to become an esports athlete, along with the attitude towards the profession of esports athlete, as well as the lifestyle patterns of the actualizer and striver, influences the decision to become an esports athlete. Furthermore, the management strategies of esports associations and the managerial style of executives also play a role in the decision-making process to become an esports athlete. The management strategies of esports associations, the managerial style of executives and staffs can significantly impact the decision-making process for individuals considering becoming esports athletes. Conclusion. The e-sports association should prioritize the identification of professional athletes’ career growth needs and establish management strategies to meet those needs. This is essential to support athletes who are determined and committed to growing in their professional paths, ultimately leading to successful outcomes.